Female Subjectivity in Carmen Maria Machado's the Husband Stitch - M. Risky Eko Ramadanto; Suci Suryani (ELITE JOURNAL, 2023)
In a society with a patriarchal system, females are subordinate to males and have limited access and freedom. Females are pressured and controlled so they are limited in their movement and they try to show female subjectivity. Carmen Maria Machado narrates the unnamed female protagonist, husband, and only son in her first debut book, Her Body and Other Parties (2017). This anthology book is awarded the Shirley Jackson Award in 2017. This research is based on Post-Structural Feminism theory, the concept of subjectivity, and the concept of resistance. The method in this study is the descriptive method. Dialogue between characters and the author's narrative are data from a short story that will be analyzed in this study. This study illustrates that female subjectivity is a way to show the existence of selfhood and personality. The trigger for the emergence of female subjectivity is the oppression experienced by the unnamed female protagonist. The female protagonist does verbal and avoidance resistance over her husband and her son. Here, Machado gives the women voices they need. Keywords: Carmen Maria Machado, Identity, Subjectivity, Post-Structural Feminism